Ludic strategy as a mediator of education in genetics in a public school (Research, Society and Development, 2021)
The present work aimed to evaluate the contributions of a game called "pedagogical trail" associated with the expository class, as a teaching tool in genetics, in high school. the work was divided into two stages: application of theoretical classes and playful strategy “pedagogical trail”. before and after the application of the lecture and the playful strategy, a pre-test and a post-test were applied, respectively. for the execution of the ludic strategy, the students were divided into 2 groups, each group selected a member responsible for the team, the same one rolled the dice and obtained a number, after the dice was cast, selected a question contained in the box at random about the content taught in class, if the team got the answer right, the group advanced the number of houses obtained. there was an increase in the percentage of correct answers, going from 22% in the pre-test to 87% in the post-test. the playful strategy carried out after the theoretical class contributed to the construction of knowledge of students in the 2nd year of high school, related to genetics subjects.